El costo de uso del capital y la inversión en Colombia 1990 – 2007 (2013)
This paper presents the construction of the use cost of capital for the Colombian economy in 1990-2007. Then, this calculation is contrasted with the dynamic of investment in the same period. It is found that the relation between investment and use cost of capital is very narrow, and it is proved that the large growth of investment in the last periods is associated with low and stable levels of the use cost of capital.